Measuring schistosomiasis case management of the health services in Ghana and Mali - Van Der Werf, M.J.; De Vlas, S.J.; Landouré, A.; Bosompem, K.M.; Habbema, J.D.F. (Tropical Medicine and International Health, 2004)
The World Health Organization recommends passive case detection by regular health services as a minimum strategy for schistosomiasis morbidity control. To evaluate preparedness of the health systems in Ghana and Mali, we presented four clinical scenarios, two with blood in urine (main early symptom of Schistosoma haematobium) and two with (bloody) diarrhoea (main early symptom of S. mansoni), to health workers. We requested the health personnel for an initial diagnosis and case management strategy without providing information about our primary interest in schistosomiasis. The information was used to determine the chance that a person reporting with symptoms that might have been caused by schistosomiasis would receive praziquantel. All selected health workers participated. Their initial diagnosis was frequently S. haematobium for both scenarios with blood in urine. For the two scenarios with (bloody) diarrhoea, only few mentioned S. mansoni. At health centre level, case management in Mali mainly consisted of direct prescription of medication, whereas in Ghana health workers often referred to a hospital or requested a diagnostic test. The ultimate probability of prescribing praziquantel was relatively high for the scenarios with blood in urine, 60% in Ghana and 75% in Mali, but very low for both scenarios with (bloody) diarrhoea (<20%). Of those health care facilities that would prescribe praziquantel, 60% (Ghana) and 80% (Mali) had it in stock. In conclusion, the clinical scenario study showed that patients reporting with blood in urine will be treated with praziquantel at approximately half of the health care facilities, whereas of those presenting with (bloody) diarrhoea only few would receive treatment with praziquantel. Considering these facts, it is questionable if passive case detection is a sufficient basis for effective schistosomiasis morbidity control, especially for S. mansoni infection.
Keywords: Disease control; Ghana; Integration; Mali; Passive case detection; Primary health care; Schistosomiasis